2019
DOI: 10.1016/j.desal.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Reverse osmosis pretreatment technologies and future trends: A comprehensive review

Abstract: Recent progress in reverse osmosis (RO) technology is not limited to RO membrane materials, module designs and RO process optimization. It involves prior feed treatment which directly impacts RO system performance. The ongoing challenges of membrane fouling in RO membranes can be addressed by increasing the operational efficiency through the use of correct pretreatment options which can mitigate organic and inorganic fouling by selectively rejecting contaminants prior to reaching the RO unit. Highly polluted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
132
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 357 publications
(140 citation statements)
references
References 274 publications
0
132
0
8
Order By: Relevance
“…On the other hand, current research interests are directed towards improving self-cleaning membranes [391]. Examples include the self-cleaning membrane created through coating the RO membranes with TiO2 [392].…”
Section: Membrane Cleaningmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, current research interests are directed towards improving self-cleaning membranes [391]. Examples include the self-cleaning membrane created through coating the RO membranes with TiO2 [392].…”
Section: Membrane Cleaningmentioning
confidence: 99%
“…Many researchers are heavily concerned with improving the overall operation of the RO systems through improving the pre-treatment systems in order to minimize membrane fouling and scaling and improve the removal of suspended solids and dissolved organic matters. RO pre-treatment technologies may be either conventional including coagulationflocculation, media filtration, disinfection, scale inhibition or non-conventional such as MF, UF, and NF [145,391,[393][394][395]. As per the available literature, UF, MF and coagulation-flocculation are considered the most widely used pre-treatment technologies.…”
Section: Pre-treatment Technologiesmentioning
confidence: 99%
“…Reverse osmosis (RO) is becoming recently a powerful technology for the purification of sea, brackish and waste water [1][2][3][4]. However, one of the major limitations in efficient RO application is the membrane scaling [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, during the formation of fouling layers on the membrane surface can beg and generate the back diffusion of dissolved salt ions which generates an increase in the concentration of salt ions on the side of the membrane surface. Results revealed that the membrane performcae may change due to organic and inorganic matter in water during osmosis process, which needs to tackle by modifying the membrane with advanced material (Anis et al, 2019;Badruzzaman et al, 2019;Croll et al, 2019;Ghaemi and Khodakarami, 2019;Ghaseminezhad et al, 2019;Joseph and Damodaran, 2019;Liu et al, 2019;Nguyen et al, 2019;Rehman et al, 2019;Shakeri et al, 2019;Tang et al, 2019;Weinman et al, 2019;Zou et al, 2019).…”
Section: Atomic Absorption Spectrometry (Aas) Resultsmentioning
confidence: 99%